The Foxfire book of Appalachian women : stories of landscape and community in the mountain South - Ahrens, Kami (The University of North Carolina Press, 2023)
"Pulled from the vast Foxfire archive, ... [some] twenty-one oral histories from southern Appalachian women whose remarkable narratives illuminate a diverse regional culture held together by the threads that are woven between women and place, and through generations. These stories, told sometimes with humor, sometimes with sadness, but always with a gripping rawness and honesty, recount women's lived experiences from 1967 to the present, from Georgia and Alabama into Tennessee and the Carolinas"--